2020
DOI: 10.1002/ece3.6591
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of grazing intensity on macroelements and microelements in grassland soil and plants in Inner Mongolia Grazing alters nutrient dynamics of grasslands

Abstract: Grazing is a traditional grassland management technique and greatly alters ecosystem nutrient cycling. The effects of grazing intensity on the nutrient dynamics of soil and plants in grassland ecosystems remain uncertain, especially among microelements. A 2‐year field grazing experiment was conducted in a typical grassland with four grazing intensities (ungrazed control, light, moderate, and heavy grazing) in Inner Mongolia, China. Nutrient concentration was assessed in soil and three dominant plant species (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(85 reference statements)
2
9
0
Order By: Relevance
“…Our livestock density estimates in MKGR were 0.02 cattle ha −1 in moderately grazed hunting block and 0.05-0.10 cattle ha −1 in the intensively grazed hunting block. Our findings align with previous studies by [63,[63][64][65] who found grazing increased soil compaction and reduced the ability of water to enter the soil of Mongolia and Nigeria.…”
Section: Reduced Soil Infiltration and Penetration In Non-operational Wildlife Hunting Blockssupporting
confidence: 93%
“…Our livestock density estimates in MKGR were 0.02 cattle ha −1 in moderately grazed hunting block and 0.05-0.10 cattle ha −1 in the intensively grazed hunting block. Our findings align with previous studies by [63,[63][64][65] who found grazing increased soil compaction and reduced the ability of water to enter the soil of Mongolia and Nigeria.…”
Section: Reduced Soil Infiltration and Penetration In Non-operational Wildlife Hunting Blockssupporting
confidence: 93%
“…Total nitrogen (T-N) content was determined using the Kjeldahl Method ( Roth et al, 2014 ), while ammonium nitrogen content in a KCl (2 mol/L) extract was measured using the indophenol blue colorimetric method ( Ye et al, 2017 ). Total phosphorus (T-P) and available phosphorus (A-P) concentrations were measured using an UV-2700 ultraviolet spectrophotometer ( Hou et al, 2020 ), while the concentration of total potassium (T-K), total calcium (T-Ca), and total magnesium (T-Mg) were measured using flame photometry ( Mishra et al, 2020 ). Available iron (A-Fe), available manganese (A-Mn), and available zinc (A-Zn) were extracted with a solution containing nitric acid, hydrogen peroxide, and hydrofluoric acid in a 6:2:2 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, some microelements with essential biological functions (Marschner & Kalbitz 2003;Bowker 2006) are required in smaller amounts by plants (<100 mg•kg -1 dry weight; e.g., Cu, Fe, Mn, and Zn;DalCorso et al 2014). These elements are involved in plant metabolic processes (Hansch & Mendel 2009;Hou et al 2020b), regulate plant growth and physiological activity (DalCorso et al 2014;Hou et al 2020b), ensure the organic matter cycle, and maintain soil functionality (Memoli et al 2018). Moreover, they are also components of enzyme prosthetic groups that catalyze redox processes, form enzyme-substrate complexes, and enhance enzyme reactions (Radujkovic et al 2021).…”
Section: Introductionmentioning
confidence: 99%